Trilobites epipelágicos del Ordovícico de Perú y Bolivia - Gutiérrez Marco, Juan Carlos (2015)
[ENG] Epipelagic telephinid trilobites rarely occur in the Ordovician of South America, being represented by few specimens recorded from the Argentinian Precordillera, the Famatina Basin, eastern Puna and Cordillera Oriental. We here report the northernmost occurrences of the genera Carolinites and Oopsites in the Central Andean Basin, coming from the Lower Ordovician rocks of the Sella Formation of southern Bolivia (Carolinites genacinaca Ross s.l.) and from the San José Formation of southwestern Peru (Oopsites sp. nov). The scarce record of these telephinids has been related to warm water currents, that sporadically moving southwards along the Gondwanan margin, carrying palaeotropical trilobites into more temperate to cool‐water higher palaeolatitudes.